Relationship between subjective voice complaints and acoustic assessment of fundamental frequency in elementary school teachers of Isfahan - Fariba Mogjiri; Faezeh Azamiyan; Ahmad Salehi (Vesnu Publications, 2012)
Introduction: Studies have shown that teachers are at high risk of developing voice disorders. This implies that, as a group, they may have more urgent priorities for inclusion in prevention and treatment programs. In the first place, such questions as whether teachers are at risk for voice disorder or not and, if it is the case, which symptoms are to be observed must be answered. Unfortunately, limited number of available speech-therapy clinics and unavailability of instrumental voice measurement make it impossible to conduct a comprehensive voice assessment for teachers in Iran. Teachers have a pivotal role in education and teacher's vocal quality affects teaching and student's learning directly. Thus, developing and applying subjective assessment tools that have sufficient correlation with instrumental assessment seem to be necessary. The purpose of this study was to determine relationship between subjective voice complaints and acoustic assessment of fundamental frequency in elementary school teachers in Isfahan. Materials & Methods: At the beginning of this cross-sectional descriptive study, a literature review was conducted to compile common vocal complaints concerning fundamental frequency. These complaints were given to 95 teachers who have been selected through random cluster sampling in the form of a checklist. Subjects were first asked to rate their voices according to the checklist and subsequently to undergo an instrumental analysis of fundamental frequency. The correlation between reported symptoms and fundamental frequency amounts were then calculated. Results: This study showed that all of complaints had a significant correlation with obtained fundamental frequencies. Conclusion: Although all complaints had a significant correlation with fundamental frequency, it is suggested that clinicians use other types of voice assessment along with these subjective complaints. Keywords: Voice disorder, Subjective assessment, Acoustic assessment, Vocal complaints, Fundamental frequency